The Influence Of Firm Size, Profitability, Managerial Ownership, Audit Committee, And Accounting Firm Size On Fee Audit - Wahyuningtyas, Yessy Pradina; Zaky, Achmad (Telaah Ilmiah Akuntansi dan Perpajakan, 2026)
This research aims to analyze the impact of company size, profitability, managerial ownership, audit committee, and accounting firm size on audit fees. This research is a quantitative analysis of a sample of 74 finance-sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The employed methodology is panel data regression analysis using a random-effects model (REM). The research findings indicate that both company size and the accounting firm positively affect audit fees; however, profitability, managerial ownership, and the audit committee do not. These findings support resource dependence theory, which posits that as the size of both the company and the accounting firm increases, the complexity of required audit procedures increases, thereby raising audit fees. These findings also have implications for companies and accounting firms of varying sizes when evaluating relevant factors in audit fee negotiations.